Quantitative methods for business - Anderson, David R. (David Ray) 1941-; Sweeney, Dennis J.; Williams, Thomas A. (Thomas Arthur) 1944-; Camm, Jeffrey D. 1958-; Martin, Kipp (South-Western, Cengage ‪Learning, 2013)
Readers don't need to be a mathematician to understand and maximize the power of quantitative methods! Written for the future or current business professional, QUANTITATIVE METHODS FOR BUSINESS, 12E, International Edition by a powerhouse, award-winning author team makes it easy for readers to understand how to most effectively use quantitative methods to make intelligent successful decisions. The book's hallmark problem-scenario approach guides readers through the application of mathematical concepts and techniques, while memorable examples illustrate how and when to use the methods. Readers discover everything needed for success in working with quantitative methods, from a strong managerial orientation to instant online access to Excel worksheets for text examples; The Management Scientist v6.0 and TreePlan; Crystal Ball; Premium Solver for Excel, and LINGO.